1990
DOI: 10.1128/jvi.64.5.2407-2410.1990
|View full text |Cite
|
Sign up to set email alerts
|

The average number of molecules of Epstein-Barr nuclear antigen 1 per cell does not correlate with the average number of Epstein-Barr virus (EBV) DNA molecules per cell among different clones of EBV-immortalized cells

Abstract: Epstein-Barr nuclear antigen 1 (EBNA-1) is the only viral protein required to support latent replication of Epstein-Barr virus (EBV). To assess the likelihood that EBNA-1 regulates the amount of EBV DNA in a cell, we measured the average numbers of EBNA-1 molecules and EBV DNA molecules per cell in different clones of cells. The amount of EBNA-1 protein present in recently established lymphoblastoid cell lines was measured with affinity-purified anti-EBNA-l antibodies, and viral DNA was measured by nucleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Moreover, since the EBNA1 and EBNA3 mRNAs are derived from the same transcription unit, in which the EBNA1 coding exon is downstream of those for the EBNA3s, the presence of Sal EBV EBNA1 in the apparent absence of detectable EBNA3A and EBNA3B from the same genomes (EBNA3Cs encoded by the Sal and Akata EBV isolates are indistinguishable by immunoblotting) may be further evidence of a posttranscriptional mechanism of action, possibly one that regulates alternative splicing. Interestingly, this apparent maintenance of specific EBNA1 levels is consistent with an earlier report that the number of EBNA1 molecules per cell is relatively constant (a less than 2-fold variance) within B-cell lines supporting latency III, despite the fact that the EBV genome copy number among these lines varied widely and up to 40-fold (62).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, since the EBNA1 and EBNA3 mRNAs are derived from the same transcription unit, in which the EBNA1 coding exon is downstream of those for the EBNA3s, the presence of Sal EBV EBNA1 in the apparent absence of detectable EBNA3A and EBNA3B from the same genomes (EBNA3Cs encoded by the Sal and Akata EBV isolates are indistinguishable by immunoblotting) may be further evidence of a posttranscriptional mechanism of action, possibly one that regulates alternative splicing. Interestingly, this apparent maintenance of specific EBNA1 levels is consistent with an earlier report that the number of EBNA1 molecules per cell is relatively constant (a less than 2-fold variance) within B-cell lines supporting latency III, despite the fact that the EBV genome copy number among these lines varied widely and up to 40-fold (62).…”
Section: Discussionsupporting
confidence: 90%
“…By transfecting LCL expressing wild‐type EBNA1 with an EBNA1ΔGA expression construct and vice versa, the amount of EBNA1 protein derived from the expression construct could be directly correlated with endogenous EBNA1. Endogenous EBNA1 is known to be expressed in a very narrow range at 25,000–44,000 molecules per cell in LCL 27. These experiments showed that NGF‐R‐sorted cells expressed at least 60‐fold more plasmid‐encoded than endogenous EBNA1 protein (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Antibodies against EBNA-1. Affinity-purified rabbit antibodies specific for the carboxyl-terminal domain of EBNA-1 were prepared as described previously (37).…”
Section: Methodsmentioning
confidence: 99%